Analysis of Efficacy and Safety of Tick-Borne Encephalitis Vaccines - T. Yu. Kozlova; L. M. Khantimirova; A. V. Rukavishnikov; V. A. Shevtsov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
This article provides a review on efficacy and safety of tick-borne encephalitis vaccines licensed in the Russian Federation. It highlights  that both Russian and imported tick-borne encephalitis vaccines  demonstrate high immunogenicity, safety and epidemiological  effectiveness in regions with high vaccine coverage. All licensed tick- borne encephalitis vaccines meet interchangeability criteria in terms of  indications for use (with due regard to age limits), medical  contraindications, vaccination schedules, vaccine composition, as well as safety, immunological activity and efficacy parameters. Timely and  specific prophylaxis help reduce the incidence of tick-borne encephalitis  in endemic regions.